Vickers Hardness Mechanical Models and Thermoplastic Polymer Injection-Molded Products’ Static Friction Coefficients - Tetsuo Takayama (Journal of Manufacturing and Materials Processing, 2024)
The surface mechanical properties of thermoplastics are crucially important for evaluating molded products’ vulnerability to scratching. Because surface mechanical properties reflect material performance directly in terms of durability and frictional behavior, understanding and modeling them is important for industry and research. This emphasizes the surface mechanical properties of Vickers hardness and the static friction coefficient, with attempts to model them as functions of stress at yield initiation. Vickers hardness can be related to the compressive stress at yield initiation. The static friction coefficient can be modeled as a function of the surface shear strength and Vickers hardness. This research has improved our understanding of thermoplastics’ surface mechanical properties and has enabled the prediction of the scratch performance of molded products and the provision of effective indicators for material design.